2018
DOI: 10.1080/13691457.2018.1539836
|View full text |Cite
|
Sign up to set email alerts
|

Inter-European social workers’ mobility within a dynamic social work and immigration policy context: a case study of England

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Social workers relocate to other countries to undertake professional practice and this phenomenon has recently become more common among the Anglophone countries, as some existing studies have demonstrated (Bartley and Beddoe, 2018; Beddoe et al, 2012; Brown et al, 2014; Hanna and Lyons, 2016; Hussein, 2020; Modderman et al, 2020). One of the reasons for this growth is that countries like the UK, Australia, New Zealand and Canada have a shared tradition of recruiting overseas educated social workers to fill their labour shortages (Modderman et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Social workers relocate to other countries to undertake professional practice and this phenomenon has recently become more common among the Anglophone countries, as some existing studies have demonstrated (Bartley and Beddoe, 2018; Beddoe et al, 2012; Brown et al, 2014; Hanna and Lyons, 2016; Hussein, 2020; Modderman et al, 2020). One of the reasons for this growth is that countries like the UK, Australia, New Zealand and Canada have a shared tradition of recruiting overseas educated social workers to fill their labour shortages (Modderman et al, 2017).…”
Section: Introductionmentioning
confidence: 99%